Evaluation of hematopoietic- and neurologic-expressed sequence 1-like (HN1L) protein levels in tissue and plasma of breast cancer patients - Erturk, Elif; Sarimahmut, Mehmet; Gökgöz, Mustafa Şehsuvar; Tolunay, Sahsine (The European Research Journal, 2023)
Objectives: Breast cancer is the second leading cause of cancer deaths among women. Therefore, there is a need for new approaches that increase the success of treatment in breast cancer. Cancer stem cells (CSCs) are associated with treatment resistance and metastasis, which are important problems in cancer treatment including breast tumors. In this study, the Hematopoietic- and neurologic-expressed sequence 1-like (HN1L), also known as Jupiter microtubule associated homolog 2 (JPT2) protein levels which is involved in the self-renewal of CSCs were evaluated in common and rare breast tumor types. Methods: In this context, HN1L protein levels were measured from plasma of 17 patients and from tumor and normal tissues of 9 patients by enzyme linked immunosorbent assay method. Results: Mean HN1L levels were measured as 1.63 ± 0.88 ng/mL in plasma samples, 2.18 ± 0.75 ng/mL in tumor tissue samples and 2.71 ± 0.88 ng/mL in normal tissue samples. A significant difference was observed between mean HN1L levels in plasma and normal tissue (p < 0.05). Correlation of HN1L protein levels with clinicopathological characteristics were analyzed. Accordingly, HN1L levels were positively correlated with tumor size and invasion status (r=0.425; p < 0.05 and r=0.449; p < 0.05, respectively). Conclusions: We believe that the importance of HN1L in management of breast cancers will be demonstrated more thoroughly when further studies are conducted with increased number of patients.